Antibacterial nylon wig fiber and preparation method thereof
By adding specific ingredients to the nylon wig fibers and adopting specific preparation methods, the problem of insufficient mechanical strength and flexibility of nylon wigs and easy to breed bacteria is solved, and fiber materials with high mechanical properties and good antibacterial properties are achieved.
Patent Information
- Application Number
- CN202211657705.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-22
AI Technical Summary
The existing nylon wigs are insufficient in mechanical strength and flexibility during use, and are prone to breeding bacteria and affecting human health.
An antibacterial nylon wig fiber is adopted, and its composition includes nylon 66, polyolefin elastomer, acrylate nanocore-shell particles, maleic anhydride grafting compatibility agent, quaternary ammonium graft nanocellulose, talc powder and anatase nanoTiO2 and other components, and fibers with excellent mechanical properties and good antibacterial properties are formed through a specific preparation method.
The mechanical properties and antibacterial properties of the nylon wig are improved, so that it can maintain high antibacterial activity after multiple washes, and enhance the bactericidal effect on bacteria.
Smart Images

Figure CN116145283B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, in particular to an antibacterial nylon wig fiber and a preparation method thereof. Background Art
[0002] Wigs can modify appearance and avoid the harm and cost of perming, pulling and dyeing. They have become a must-have decoration for people with hair loss, gray hair and hair loss. The number of people who own wigs in my country has increased significantly year by year. Among them, nylon wigs are favored by more and more people. However, the current nylon wigs have many defects such as poor mechanical strength and flexibility, lack of realism, etc. In addition, during the wearing and use of wigs, wigs are in direct or indirect contact with the human body. The sweat secreted by the scalp mixed with rainwater, dust, etc. can easily breed bacteria, which is not good for human health. Summary of the invention
[0003] Purpose of the invention: In view of the above technical problems, the present invention provides an antibacterial nylon wig fiber and a preparation method thereof.
[0004] The technical solutions adopted are as follows:
[0005] An antibacterial nylon wig fiber, comprising the following components in parts by weight:
[0006] 60-80 parts of nylon 66, 20-30 parts of polyolefin elastomer, 10-15 parts of acrylic ester nano core-shell particles, 3-5 parts of maleic anhydride grafted compatibilizer, 5-15 parts of quaternary ammonium salt grafted nano cellulose, 20-30 parts of talc, 0.05-0.15 parts of anatase nano TiO2, and 0.1-0.5 parts of antistatic agent.
[0007] Furthermore, the acrylic ester nano core-shell particles have polybutyl acrylate as the core layer and poly(methyl methacrylate-co-glycidyl methacrylate-co-diacetone acrylamide) as the shell layer.
[0008] Furthermore, the preparation method of the acrylic ester nano core-shell particles is as follows:
[0009] Under a protective gas atmosphere, after the emulsifier and water are evenly mixed, butyl acrylate, 1,4-butanediol diacrylate and the first portion of the initiator solution are added, the temperature is raised to 70-80°C and stirred for reaction for 30-50 minutes, then the second portion of the initiator solution is added, and the reaction is continued for 5-15 minutes to obtain a seed monomer pre-emulsion, the core layer monomer pre-emulsion and the third portion of the initiator solution are added dropwise to the seed monomer pre-emulsion, and the reaction is stirred for 60-90 minutes after the addition is completed, the shell layer monomer pre-emulsion and the fourth portion of the initiator solution are added dropwise, and the reaction is stirred for 60-90 minutes after the addition is completed, and the obtained emulsion is frozen, thawed, demulsified, washed with water, filtered, and dried.
[0010] Furthermore, the core layer monomer pre-emulsion includes butyl acrylate, an emulsifier and allyl methacrylate.
[0011] Furthermore, the shell monomer pre-emulsion includes methyl methacrylate, glycidyl methacrylate, diacetone acrylamide and an emulsifier.
[0012] Furthermore, the emulsifier is an anionic emulsifier, preferably sodium lauryl sulfate.
[0013] Furthermore, the preparation method of the quaternary ammonium salt grafted nanocellulose is as follows:
[0014] Under a protective gas atmosphere, nanocellulose, triethylamine, and 2-bromoisobutyryl bromide are added to DMF, and the reaction is carried out at 65-75° C. for 20-25 hours to obtain an intermediate. Under a protective gas atmosphere, the intermediate, quaternary ammonium salt monomer, copper bromide, ascorbic acid, pentamethyldiethylenetriamine, and ethyl 2-bromoisobutyrate are added to DMSO, and the reaction is carried out at 40-60° C. for 18-24 hours. After the reaction is completed, dichloromethane is added, stirred, filtered, and the obtained solid is washed and dried.
[0015] Furthermore, the quaternary ammonium salt monomer is dodecyldimethylammonium methacrylate.
[0016] The present invention also provides a method for preparing antibacterial nylon wig fibers:
[0017] Nylon 66, polyolefin elastomer, acrylic ester nano core-shell particles, maleic anhydride grafted compatibilizer, quaternary ammonium salt grafted nano cellulose, talcum powder, anatase nano TiO2 and antistatic agent are mixed and melt-extruded to obtain primary fibers, which are cooled and then subjected to oiling, pulling and heat setting treatments.
[0018] Furthermore, the heat setting treatment temperature is 150-170° C. and the time is 10-20 minutes.
[0019] Beneficial effects of the present invention:
[0020] The invention provides an antibacterial nylon wig fiber. The special molecular structure of the polyolefin elastomer enables it to have excellent physical and mechanical properties (high elasticity, high elongation, good impact strength), good low temperature resistance and processing rheology. After being added, it can have a toughening and strengthening effect on nylon 66. The maleic anhydride grafted compatibilizer can improve the compatibility between the two and form a mutually discrete rubber phase that penetrates the nylon matrix, thereby effectively dispersing and absorbing energy, showing a significant improvement in toughness. Acrylic ester nano core-shell particles are rarely used to improve the mechanical strength of nylon fibers. The inventor adds diacetone acrylamide when preparing the acrylic ester nano core-shell particles, which can improve the crosslinking density, and the amide group contained in the nylon matrix has a good dispersion performance. The quaternary ammonium salt grafted nanocellulose can not only improve the mechanical strength of the nylon wig fiber, but also has good antibacterial and bactericidal properties. The hydrophobic long alkyl chain in dodecyl dimethyl ammonium methacrylate helps to penetrate and destroy the bacterial cell membrane, thereby improving the antibacterial effect. The positively charged nitrogen atom in the quaternary ammonium group is adsorbed together with the negatively charged bacterial cell wall and cell membrane through electrostatic action. The lipophilic long-chain alkyl tail is inserted into the cell membrane and combined with the protein layer and lipid layer in the cell membrane, which affects the exchange process between the bacteria and the outside world and causes the cytoplasmic contents of the bacteria to leak and eventually die. The antibacterial nylon wig fiber prepared by the present invention not only has excellent mechanical properties, but also has good antibacterial properties, and can still maintain a high antibacterial activity after repeated washing. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the nylon wig fiber prepared in Example 1 of the present invention.
[0022] Figure 2 is the growth of Escherichia coli on LB medium;
[0023] Wherein, A is the growth condition of Escherichia coli after contact culture with the nylon wig fiber prepared in Example 1 of the present invention on LB medium;
[0024] B is the growth of Escherichia coli on LB medium after contact culture with the nylon wig fiber prepared in Comparative Example 3 of the present invention;
[0025] From this comparison, it can be seen that the addition of quaternary ammonium salt grafted nanocellulose can improve the antibacterial properties of nylon wig fibers. DETAILED DESCRIPTION
[0026] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The technologies not mentioned in the present invention are all referenced to the prior art.
[0027] Embodiment 1:
[0028] An antibacterial nylon wig fiber, comprising the following components in parts by weight:
[0029] 75 parts of nylon 66, 24 parts of polyolefin elastomer POE, 15 parts of acrylic ester nano core-shell particles, 4 parts of maleic anhydride grafted POE, 12 parts of quaternary ammonium salt grafted nano cellulose, 25 parts of talc, 0.08 parts of anatase nano TiO2, and 0.2 parts of antistatic agent SAS93.
[0030] Among them, the acrylic ester nano core-shell particles have polybutyl acrylate as the core layer and poly(methyl methacrylate-co-glycidyl methacrylate-co-diacetone acrylamide) as the shell layer, and the specific preparation method is as follows:
[0031] Take 1.2g of initiator potassium persulfate and 40mL of water and add them to a beaker, stir until fully dissolved to obtain an initiator solution, and divide it into four parts;
[0032] Add 150 g of butyl acrylate, 2 g of emulsifier sodium lauryl sulfate and 0.75 g of allyl methacrylate into a beaker and stir until uniform to obtain a core layer monomer pre-emulsion;
[0033] Add 40 g of methyl methacrylate, 0.8 g of emulsifier sodium lauryl sulfate, 10 g of glycidyl methacrylate, and 2 g of diacetone acrylamide into a beaker and stir until uniform to obtain a shell monomer pre-emulsion;
[0034] Under a nitrogen atmosphere, 0.8 g of emulsifier sodium dodecyl sulfate and 140 mL of water were mixed evenly, and then 10 g of butyl acrylate, 0.05 g of 1,4-butanediol diacrylate and the first portion of the initiator solution were added. The temperature was raised to 80°C and stirred for reaction for 30 min, then the second portion of the initiator solution was added, and the reaction was continued for 10 min to obtain a seed monomer pre-emulsion. The core layer monomer pre-emulsion and the third portion of the initiator solution were added dropwise to the seed monomer pre-emulsion, and the reaction was stirred for 80 min after the addition was completed. The shell layer monomer pre-emulsion and the fourth portion of the initiator solution were added dropwise, and the reaction was stirred for 80 min after the addition was completed. The obtained emulsion was placed in a refrigerator for 24 h, thawed, demulsified, washed, filtered, and dried.
[0035] The preparation method of quaternary ammonium salt grafted nanocellulose is as follows:
[0036] Under a nitrogen atmosphere, 2 g of nanocellulose, 66 mL of triethylamine, and 26 mL of 2-bromoisobutyryl bromide were added to 200 mL of DMF, reacted at 75 ° C for 20 h, filtered, and the filter cake was transferred to a Soxhlet extractor and extracted with dichloromethane and ethanol for 24 h respectively. After drying, the intermediate was obtained. Under a nitrogen atmosphere, 1 g of the intermediate, 71.4 g of dodecyldimethylammonium methacrylate, 0.11 g of copper bromide, 0.88 g of ascorbic acid, 0.85 g of pentamethyldiethylenetriamine, and 0.72 g of ethyl 2-bromoisobutyrate were added to 250 mL of DMSO, reacted at 50 ° C for 24 h, and after the reaction, 800 mL of dichloromethane was added, stirred, filtered, and the obtained solid was washed and dried.
[0037] The preparation method of the above-mentioned antibacterial nylon wig fiber:
[0038] Nylon 66, polyolefin elastomer POE, acrylic ester nano core-shell particles, maleic anhydride grafted POE, quaternary ammonium salt grafted nano cellulose, talcum powder, anatase nano TiO2 and antistatic agent SAS93 are mixed and melt-extruded to obtain primary fibers, which are air-cooled, oiled, pulled and heat-set at 160°C for 12 minutes before being rolled up.
[0039] Embodiment 2:
[0040] An antibacterial nylon wig fiber, comprising the following components in parts by weight:
[0041] 80 parts of nylon 66, 30 parts of polyolefin elastomer POE, 15 parts of acrylic ester nano core-shell particles, 5 parts of maleic anhydride grafted POE, 15 parts of quaternary ammonium salt grafted nano cellulose, 30 parts of talc, 0.15 parts of anatase nano TiO2, and 0.5 parts of antistatic agent SAS93.
[0042] Among them, the acrylic ester nano core-shell particles have polybutyl acrylate as the core layer and poly(methyl methacrylate-co-glycidyl methacrylate-co-diacetone acrylamide) as the shell layer, and the specific preparation method is as follows:
[0043] Take 1.2g of initiator potassium persulfate and 40mL of water and add them to a beaker, stir until fully dissolved to obtain an initiator solution, and divide it into four parts;
[0044] Add 150 g of butyl acrylate, 2 g of emulsifier sodium lauryl sulfate and 0.75 g of allyl methacrylate into a beaker and stir until uniform to obtain a core layer monomer pre-emulsion;
[0045] Add 40 g of methyl methacrylate, 0.8 g of emulsifier sodium lauryl sulfate, 10 g of glycidyl methacrylate, and 2 g of diacetone acrylamide into a beaker and stir until uniform to obtain a shell monomer pre-emulsion;
[0046] Under a nitrogen atmosphere, 0.8 g of emulsifier sodium dodecyl sulfate and 140 mL of water were mixed evenly, and then 10 g of butyl acrylate, 0.05 g of 1,4-butanediol diacrylate and the first portion of the initiator solution were added. The temperature was raised to 80°C and stirred for reaction for 50 min, then the second portion of the initiator solution was added, and the reaction was continued for 15 min to obtain a seed monomer pre-emulsion. The core layer monomer pre-emulsion and the third portion of the initiator solution were added dropwise to the seed monomer pre-emulsion, and the reaction was stirred for 90 min after the addition was completed. The shell layer monomer pre-emulsion and the fourth portion of the initiator solution were added dropwise, and the reaction was stirred for 90 min after the addition was completed. The obtained emulsion was placed in a refrigerator for 24 h, thawed, demulsified, washed, filtered, and dried.
[0047] The preparation method of quaternary ammonium salt grafted nanocellulose is as follows:
[0048] Under a nitrogen atmosphere, 2 g of nanocellulose, 66 mL of triethylamine, and 26 mL of 2-bromoisobutyryl bromide were added to 200 mL of DMF, reacted at 75 ° C for 25 h, filtered, and the filter cake was transferred to a Soxhlet extractor and extracted with dichloromethane and ethanol for 24 h respectively. After drying, the intermediate was obtained. Under a nitrogen atmosphere, 1 g of the intermediate, 71.4 g of dodecyldimethylammonium methacrylate, 0.11 g of copper bromide, 0.88 g of ascorbic acid, 0.85 g of pentamethyldiethylenetriamine, and 0.72 g of ethyl 2-bromoisobutyrate were added to 250 mL of DMSO, reacted at 60 ° C for 24 h, and after the reaction, 800 mL of dichloromethane was added, stirred, filtered, and the obtained solid was washed and dried.
[0049] The preparation method of the above-mentioned antibacterial nylon wig fiber:
[0050] Nylon 66, polyolefin elastomer POE, acrylic ester nano core-shell particles, maleic anhydride grafted POE, quaternary ammonium salt grafted nano cellulose, talcum powder, anatase nano TiO2 and antistatic agent SAS93 are mixed and melt-extruded to obtain primary fibers, which are then air-cooled, oiled, pulled, and heat-set at 170°C for 20 minutes before being rolled up.
[0051] Embodiment 3:
[0052] An antibacterial nylon wig fiber, comprising the following components in parts by weight:
[0053] 60 parts of nylon 66, 20 parts of polyolefin elastomer POE, 10 parts of acrylic ester nano core-shell particles, 3 parts of maleic anhydride grafted POE, 5 parts of quaternary ammonium salt grafted nano cellulose, 20 parts of talc, 0.05 parts of anatase nano TiO2, and 0.1 parts of antistatic agent SAS93.
[0054] Among them, the acrylic ester nano core-shell particles have polybutyl acrylate as the core layer and poly(methyl methacrylate-co-glycidyl methacrylate-co-diacetone acrylamide) as the shell layer, and the specific preparation method is as follows:
[0055] Take 1.2g of initiator potassium persulfate and 40mL of water and add them to a beaker, stir until fully dissolved to obtain an initiator solution, and divide it into four parts;
[0056] Add 150 g of butyl acrylate, 2 g of emulsifier sodium lauryl sulfate and 0.75 g of allyl methacrylate into a beaker and stir until uniform to obtain a core layer monomer pre-emulsion;
[0057] Add 40 g of methyl methacrylate, 0.8 g of emulsifier sodium lauryl sulfate, 10 g of glycidyl methacrylate, and 2 g of diacetone acrylamide into a beaker and stir until uniform to obtain a shell monomer pre-emulsion;
[0058] Under a nitrogen atmosphere, 0.8 g of emulsifier sodium dodecyl sulfate and 140 mL of water were mixed evenly, and then 10 g of butyl acrylate, 0.05 g of 1,4-butanediol diacrylate and the first portion of the initiator solution were added. The temperature was raised to 70°C and stirred for reaction for 30 min, then the second portion of the initiator solution was added, and the reaction was continued for 5 min to obtain a seed monomer pre-emulsion. The core layer monomer pre-emulsion and the third portion of the initiator solution were added dropwise to the seed monomer pre-emulsion, and the reaction was stirred for 60 min after the addition was completed. The shell layer monomer pre-emulsion and the fourth portion of the initiator solution were added dropwise, and the reaction was stirred for 60 min after the addition was completed. The obtained emulsion was placed in a refrigerator for 24 h, thawed, demulsified, washed, filtered, and dried.
[0059] The preparation method of quaternary ammonium salt grafted nanocellulose is as follows:
[0060] Under a nitrogen atmosphere, 2 g of nanocellulose, 66 mL of triethylamine, and 26 mL of 2-bromoisobutyryl bromide were added to 200 mL of DMF, reacted at 65 ° C for 20 h, filtered, and the filter cake was transferred to a Soxhlet extractor and extracted with dichloromethane and ethanol for 24 h respectively. After drying, the intermediate was obtained. Under a nitrogen atmosphere, 1 g of the intermediate, 71.4 g of dodecyldimethylammonium methacrylate, 0.11 g of copper bromide, 0.88 g of ascorbic acid, 0.85 g of pentamethyldiethylenetriamine, and 0.72 g of ethyl 2-bromoisobutyrate were added to 250 mL of DMSO, reacted at 40 ° C for 18 h, and after the reaction, 800 mL of dichloromethane was added, stirred, filtered, and the obtained solid was washed and dried.
[0061] The preparation method of the above-mentioned antibacterial nylon wig fiber:
[0062] Nylon 66, polyolefin elastomer POE, acrylic ester nano core-shell particles, maleic anhydride grafted POE, quaternary ammonium salt grafted nano cellulose, talcum powder, anatase nano TiO2 and antistatic agent SAS93 are mixed and melt-extruded to obtain primary fibers, which are then air-cooled, oiled, pulled and heat-set at 150°C for 10 minutes before being rolled up.
[0063] Embodiment 4:
[0064] An antibacterial nylon wig fiber, comprising the following components in parts by weight:
[0065] 80 parts of nylon 66, 20 parts of polyolefin elastomer POE, 15 parts of acrylic ester nano core-shell particles, 3 parts of maleic anhydride grafted POE, 15 parts of quaternary ammonium salt grafted nano cellulose, 20 parts of talc, 0.15 parts of anatase nano TiO2, and 0.1 parts of antistatic agent SAS93.
[0066] Among them, the acrylic ester nano core-shell particles have polybutyl acrylate as the core layer and poly(methyl methacrylate-co-glycidyl methacrylate-co-diacetone acrylamide) as the shell layer, and the specific preparation method is as follows:
[0067] Take 1.2g of initiator potassium persulfate and 40mL of water and add them to a beaker, stir until fully dissolved to obtain an initiator solution, and divide it into four parts;
[0068] Add 150 g of butyl acrylate, 2 g of emulsifier sodium lauryl sulfate and 0.75 g of allyl methacrylate into a beaker and stir until uniform to obtain a core layer monomer pre-emulsion;
[0069] Add 40 g of methyl methacrylate, 0.8 g of emulsifier sodium lauryl sulfate, 10 g of glycidyl methacrylate, and 2 g of diacetone acrylamide into a beaker and stir until uniform to obtain a shell monomer pre-emulsion;
[0070] Under a nitrogen atmosphere, 0.8 g of emulsifier sodium dodecyl sulfate and 140 mL of water were mixed evenly, and then 10 g of butyl acrylate, 0.05 g of 1,4-butanediol diacrylate and the first portion of the initiator solution were added. The temperature was raised to 80°C and stirred for reaction for 30 min, then the second portion of the initiator solution was added, and the reaction was continued for 15 min to obtain a seed monomer pre-emulsion. The core layer monomer pre-emulsion and the third portion of the initiator solution were added dropwise to the seed monomer pre-emulsion, and the reaction was stirred for 60 min after the addition was completed. The shell layer monomer pre-emulsion and the fourth portion of the initiator solution were added dropwise, and the reaction was stirred for 90 min after the addition was completed. The obtained emulsion was placed in a refrigerator for 24 h, thawed, demulsified, washed, filtered, and dried.
[0071] The preparation method of quaternary ammonium salt grafted nanocellulose is as follows:
[0072] Under a nitrogen atmosphere, 2 g of nanocellulose, 66 mL of triethylamine, and 26 mL of 2-bromoisobutyryl bromide were added to 200 mL of DMF, reacted at 65 ° C for 25 h, filtered, and the filter cake was transferred to a Soxhlet extractor and extracted with dichloromethane and ethanol for 24 h respectively. After drying, the intermediate was obtained. Under a nitrogen atmosphere, 1 g of the intermediate, 71.4 g of dodecyldimethylammonium methacrylate, 0.11 g of copper bromide, 0.88 g of ascorbic acid, 0.85 g of pentamethyldiethylenetriamine, and 0.72 g of ethyl 2-bromoisobutyrate were added to 250 mL of DMSO, reacted at 40 ° C for 24 h, and after the reaction, 800 mL of dichloromethane was added, stirred, filtered, and the obtained solid was washed and dried.
[0073] The preparation method of the above-mentioned antibacterial nylon wig fiber:
[0074] Nylon 66, polyolefin elastomer POE, acrylic ester nano core-shell particles, maleic anhydride grafted POE, quaternary ammonium salt grafted nano cellulose, talcum powder, anatase nano TiO2 and antistatic agent SAS93 are mixed and melt-extruded to obtain primary fibers, which are then air-cooled, oiled, pulled, and heat-set at 150°C for 20 minutes before being rolled up.
[0075] Embodiment 5:
[0076] An antibacterial nylon wig fiber, comprising the following components in parts by weight:
[0077] 60 parts of nylon 66, 30 parts of polyolefin elastomer POE, 10 parts of acrylic ester nano core-shell particles, 5 parts of maleic anhydride grafted POE, 5 parts of quaternary ammonium salt grafted nano cellulose, 30 parts of talc, 0.05 parts of anatase nano TiO2, and 0.5 parts of antistatic agent SAS93.
[0078] Among them, the acrylic ester nano core-shell particles have polybutyl acrylate as the core layer and poly(methyl methacrylate-co-glycidyl methacrylate-co-diacetone acrylamide) as the shell layer, and the specific preparation method is as follows:
[0079] Take 1.2g of initiator potassium persulfate and 40mL of water and add them to a beaker, stir until fully dissolved to obtain an initiator solution, and divide it into four parts;
[0080] Add 150 g of butyl acrylate, 2 g of emulsifier sodium lauryl sulfate and 0.75 g of allyl methacrylate into a beaker and stir until uniform to obtain a core layer monomer pre-emulsion;
[0081] Add 40 g of methyl methacrylate, 0.8 g of emulsifier sodium lauryl sulfate, 10 g of glycidyl methacrylate, and 2 g of diacetone acrylamide into a beaker and stir until uniform to obtain a shell monomer pre-emulsion;
[0082] Under a nitrogen atmosphere, 0.8 g of emulsifier sodium dodecyl sulfate and 140 mL of water were mixed evenly, and then 10 g of butyl acrylate, 0.05 g of 1,4-butanediol diacrylate and the first portion of the initiator solution were added. The temperature was raised to 70°C and stirred for reaction for 50 min, then the second portion of the initiator solution was added, and the reaction was continued for 5 min to obtain a seed monomer pre-emulsion. The core layer monomer pre-emulsion and the third portion of the initiator solution were added dropwise to the seed monomer pre-emulsion, and the reaction was stirred for 90 min after the addition was completed. The shell layer monomer pre-emulsion and the fourth portion of the initiator solution were added dropwise, and the reaction was stirred for 60 min after the addition was completed. The obtained emulsion was placed in a refrigerator for 24 h, thawed, demulsified, washed, filtered, and dried.
[0083] The preparation method of quaternary ammonium salt grafted nanocellulose is as follows:
[0084] Under a nitrogen atmosphere, 2 g of nanocellulose, 66 mL of triethylamine, and 26 mL of 2-bromoisobutyryl bromide were added to 200 mL of DMF, reacted at 75 ° C for 20 h, filtered, and the filter cake was transferred to a Soxhlet extractor and extracted with dichloromethane and ethanol for 24 h respectively. After drying, the intermediate was obtained. Under a nitrogen atmosphere, 1 g of the intermediate, 71.4 g of dodecyldimethylammonium methacrylate, 0.11 g of copper bromide, 0.88 g of ascorbic acid, 0.85 g of pentamethyldiethylenetriamine, and 0.72 g of ethyl 2-bromoisobutyrate were added to 250 mL of DMSO, reacted at 60 ° C for 18 h, and after the reaction, 800 mL of dichloromethane was added, stirred, filtered, and the obtained solid was washed and dried.
[0085] The preparation method of the above-mentioned antibacterial nylon wig fiber:
[0086] Nylon 66, polyolefin elastomer POE, acrylate nano core-shell particles, maleic anhydride grafted POE, quaternary ammonium salt grafted nano cellulose, talcum powder, anatase nano TiO2 and antistatic agent SAS93 are mixed and melt-extruded to obtain primary fibers, which are then air-cooled, oiled, pulled, and heat-set at 170°C for 10 minutes before being rolled up.
[0087] Comparative Example 1:
[0088] The method is basically the same as Example 1, except that no acrylic ester nano core-shell particles are added.
[0089] Comparative Example 2:
[0090] The method is basically the same as Example 1, except that diacetone acrylamide is not added during the preparation of the acrylate nano core-shell particles.
[0091] Comparative Example 3:
[0092] The method is basically the same as Example 1, except that no quaternary ammonium salt is added to graft the nanocellulose.
[0093] Performance Testing:
[0094] ① The antibacterial nylon wig fibers prepared in Examples 1-5 and Comparative Examples 1-4 of the present invention are used as samples;
[0095] With reference to GB / T14337-2008 "Test Method for Tensile Properties of Chemical Fibers and Short Fibers", the mechanical strength of the samples was tested using a fiber strength and elongation tester. The test results are shown in Table 1 below:
[0096] Table 1:
[0097]
[0098] It can be seen from Table 1 above that the antibacterial nylon wig fiber prepared by the present invention has excellent mechanical properties.
[0099] ② The antibacterial nylon wig fiber prepared in Example 1 of the present invention is used as a sample;
[0100] Referring to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the antibacterial rate of the test sample was tested. The test results are shown in Table 2 below:
[0101] Table 2:
[0102]
[0103] It can be seen from Table 2 above that the antibacterial wig prepared by the present invention has good antibacterial performance and can still maintain a high antibacterial activity after multiple washings.
[0104] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An antibacterial nylon wig fiber, characterized in that: The spinning raw materials include the following components in parts by weight: 60-80 parts of nylon 66, 20-30 parts of polyolefin elastomer, 10-15 parts of acrylic ester nano core-shell particles, 3-5 parts of maleic anhydride grafted compatibilizer, 5-15 parts of quaternary ammonium salt grafted nano cellulose, 20-30 parts of talc, 0.05-0.15 parts of anatase nano TiO2, and 0.1-0.5 parts of antistatic agent; The acrylic ester nano core-shell particles are composed of polybutyl acrylate as the core layer and poly(methyl methacrylate- co -Glycidyl Methacrylate- co -diacetone acrylamide) as the shell layer; The quaternary ammonium salt grafted nanocellulose is grafted with dodecyldimethylammonium methacrylate as a quaternary ammonium salt monomer.
2. The antibacterial nylon wig fiber according to claim 1, characterized in that: The preparation method of the acrylic acid ester nano core-shell particles is as follows: Under a protective gas atmosphere, after the emulsifier and water are evenly mixed, butyl acrylate, 1,4-butanediol diacrylate and the first portion of the initiator solution are added, the temperature is raised to 70-80°C and stirred for reaction for 30-50 minutes, then the second portion of the initiator solution is added, and the reaction is continued for 5-15 minutes to obtain a seed monomer pre-emulsion, the core layer monomer pre-emulsion and the third portion of the initiator solution are added dropwise to the seed monomer pre-emulsion, and the reaction is stirred for 60-90 minutes after the addition is completed, the shell layer monomer pre-emulsion and the fourth portion of the initiator solution are added dropwise, and the reaction is stirred for 60-90 minutes after the addition is completed, and the obtained emulsion is frozen, thawed, demulsified, washed with water, filtered, and dried.
3. The antibacterial nylon wig fiber according to claim 2, characterized in that: The core layer monomer pre-emulsion comprises butyl acrylate, an emulsifier and allyl methacrylate.
4. The antibacterial nylon wig fiber according to claim 2, characterized in that: The shell monomer pre-emulsion comprises methyl methacrylate, glycidyl methacrylate, diacetone acrylamide and an emulsifier.
5. The antibacterial nylon wig fiber according to claim 2, characterized in that: The emulsifier is an anionic emulsifier.
6. The antibacterial nylon wig fiber according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt grafted nanocellulose is as follows: Under a protective gas atmosphere, nanocellulose, triethylamine, and 2-bromoisobutyryl bromide are added to DMF, and the reaction is carried out at 65-75° C. for 20-25 hours to obtain an intermediate. Under a protective gas atmosphere, the intermediate, quaternary ammonium salt monomer, copper bromide, ascorbic acid, pentamethyldiethylenetriamine, and ethyl 2-bromoisobutyrate are added to DMSO, and the reaction is carried out at 40-60° C. for 18-24 hours. After the reaction is completed, dichloromethane is added, stirred, filtered, and the obtained solid is washed and dried.
7. A method for preparing the antibacterial nylon wig fiber according to any one of claims 1 to 6, characterized in that: Nylon 66, polyolefin elastomer, acrylic ester nano core-shell particles, maleic anhydride grafted compatibilizer, quaternary ammonium salt grafted nano cellulose, talcum powder, anatase nano TiO2 and antistatic agent are mixed and melt-extruded to obtain primary fibers, which are then cooled and subjected to oiling, traction and heat setting treatments.
8. The method for preparing the antibacterial nylon wig fiber according to claim 7, characterized in that: The heat setting treatment temperature is 150-170°C and the time is 10-20 minutes.
Citation Information
Patent Citations
Inflaming-retarding antibacterial nylon wig fibers and preparation method thereof
CN111472062A
Polymer blend fiber
JP2007217838A
Cited By
A method for preparing a medicated hair fiber
CN122669505A